2022
DOI: 10.3390/ijms23158572
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia in Pregnancy-Associated Oxidative Stress Augments Altered Placental Glucose Transporter 1 Trafficking via AMPKα/p38MAPK Signaling Cascade

Abstract: GLUT1, being a ubiquitous transporter isoform, is considered primarily responsible for glucose uptake during glycolysis. However, there is still uncertainty about the regulatory mechanisms of GLUT1 in hyperglycemia in pregnancy (HIP, PGDM, and GDM) accompanied by abnormal oxidative stress responses. In the present study, it was observed that the glycolysis was enhanced in GDM and PGDM pregnancies. In line with this, the antioxidant system was disturbed and GLUT1 expression was increased due to diabetes impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 64 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…Mechanistically, hyperglycemia upregulates GLUT1 in the trophoblasts via the AMPKα-p38MAPK signaling cascade, thereby regulating placental transport function. 192 Several studies confirmed increased expression and activity of GLUT1 in the placental basement membrane but not the syncytial microvillous in women with GDM. [194][195][196] However, certain studies confirmed altered GLUT1 expression in patients with pregestational diabetes mellitus (PGDM) but not GDM.…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 96%
See 4 more Smart Citations
“…Mechanistically, hyperglycemia upregulates GLUT1 in the trophoblasts via the AMPKα-p38MAPK signaling cascade, thereby regulating placental transport function. 192 Several studies confirmed increased expression and activity of GLUT1 in the placental basement membrane but not the syncytial microvillous in women with GDM. [194][195][196] However, certain studies confirmed altered GLUT1 expression in patients with pregestational diabetes mellitus (PGDM) but not GDM.…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 96%
“…Wang et al. confirmed that D‐glucose 6‐phosphate, Beta‐D‐Fructose 6‐phosphate, and D‐Fructose 1,6‐bisphosphate were significantly increased in the insulin‐controlled GDM group 192 . However, Zhang et al.…”
Section: Glycolysis In Pathological Pregnancymentioning
confidence: 97%
See 3 more Smart Citations